2013
DOI: 10.1155/2013/613086
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Psoriasis and Pharmacogenetics of Biological Drugs

Abstract: Psoriasis is a chronic inflammatory disease of the skin. The causes of psoriasis are unknown, although family and twin studies have shown genetic factors to play a key role in its development. The many genes associated with psoriasis and the immune response include TNFα, IL23, and IL12. Advances in knowledge of the pathogenesis of psoriasis have enabled the development of new drugs that target cytokines (e.g., etanercept, adalimumab, and infliximab, which target TNFα, and ustekinumab, which targets the p40 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 101 publications
1
69
0
Order By: Relevance
“…In the present study, the efficacy of the TNF-α inhibitors etanercept and infliximab in plaque psoriasis therapy has been clearly demonstrated, in agreement with previous studies (2)(3)(4)(5)(6). Furthermore, concerning the small number of infliximab-treated cases or female patients, this study revealed notable observations regarding correlations among pro-inflammatory genes, anti-TNF-α treatment type and gender.…”
Section: A B C Dsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the efficacy of the TNF-α inhibitors etanercept and infliximab in plaque psoriasis therapy has been clearly demonstrated, in agreement with previous studies (2)(3)(4)(5)(6). Furthermore, concerning the small number of infliximab-treated cases or female patients, this study revealed notable observations regarding correlations among pro-inflammatory genes, anti-TNF-α treatment type and gender.…”
Section: A B C Dsupporting
confidence: 92%
“…IL-33 can act as both a pro-and anti-inflammatory factor (38). It is currently considered that biologically active IL-33 is released during necrosis as an endogenous danger or 'alarm' signal; during apoptosis, IL-33 is cleaved and inactivated (3,27). The present results indicate that the pro-inflammatory function of IL-33 in psoriatic skin can be inhibited by TNF-α blockers, in agreement with previous studies by Balato et al (25) and Li et al (39) which have described the regulation of IL33 by TNF-α.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known regarding the interaction between genetics and biological drugs in relation to psoriasis. 5 Pharmacogenetics has been more thoroughly investigated in inflammatory bowel disease and rheumatoid arthritis, where polymorphisms in genes encoding Toll-like receptors (TLRs) and NOD-like receptors have been found to be associated with response to anti-TNF drugs. [6][7][8][9][10] Nuclear factor-κB plays a major role in controlling inflammation and is an important regulator of pathways leading to expression of cytokines in psoriasis, including IL-1β (http://www.bu.edu/nf-kb/generesources/target-genes/).…”
Section: Introductionmentioning
confidence: 99%
“…Classic genome-wide linkage analysis has indicated that there are nine loci on different chromosomes associated with psoriasis, including those containing genes whose products serve a role in inflammation, such as AKT (29)(30)(31)(32). These loci are associated with the NF-κB and tumor necrosis factor (TNF)-α signaling pathways (29).…”
Section: Discussionmentioning
confidence: 99%